The Effect of Eco-Consciousness Workshop on Students’ Environmental Consciousness - Akın, Beril Salman; Koca, Fatma Nur; Karacasoy, Ayşe Rumeysa (GLOBETS 2023 Educational Technology and Science Research, 2024)
The increasing pressure on the environment and natural resources makes it necessary to have a detailed understanding of these issues in educational programs. Environmental education is now a part of updated curricula, aimed at helping people to understand environmental problems, cope with them, and create a more sustainable world for future generations. Recent research highlights the importance of interactive learning in sustainable environmental education programs, which should not be passive but actively foster skills, attitudes, values, and understanding in this field. It is therefore crucial to create more interactive environments within environmentally oriented educational courses, both inside and outside the classroom, to enable students to take an active role. Interactive learning can encourage more effective, independent, and motivated learning among students, fostering deeper understanding, critical thinking, and problem-solving skills. Eco-conscious workshops are often organized to enhance environmental education and awareness, serving as significant interactive learning environments, and providing participants with knowledge about environmental issues, sustainability, and natural resource management, thereby contributing to the development of environmental consciousness. This study aims to develop a methodology for preparing and implementing Eco-Conscious workshops following the 5E educational model. The methodology is illustrated with examples of Eco-Conscious workshops, including workshop descriptions, work plans, and assessment approaches.